2014
DOI: 10.1016/j.jadohealth.2013.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Are Tobacco Control Policies Effective in Reducing Young Adult Smoking?

Abstract: Purpose We examined the influence of tobacco control program funding, smoke-free air laws, and cigarette prices on young adult smoking outcomes. Methods We use a natural experimental design approach that uses the variation in tobacco control policies across states and over time to understand their influence on tobacco outcomes. We combine individual outcome data with annual state-level policy data to conduct multivariable logistic regression models, controlling for an extensive set of sociodemographic factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…The successes in decreased tobacco use in California is likely due to concerted efforts of early and comprehensive tobacco prevention and control (Messer & Pierce, 2010; Pierce et al, 2010). Other states have also had successes in reducing prevalence of cigarette use and related morbidity and mortality (Farrelly et al, 2013, 2014; Kuiper, Nelson, & Schooley, 2005). It was expected that California would exhibit greater success in tobacco control than the rest of the US, however the differential and strong effects for racial/ethnic minority groups is both striking and an indicator of success in reducing tobacco disparities in California.…”
Section: Discussionmentioning
confidence: 99%
“…The successes in decreased tobacco use in California is likely due to concerted efforts of early and comprehensive tobacco prevention and control (Messer & Pierce, 2010; Pierce et al, 2010). Other states have also had successes in reducing prevalence of cigarette use and related morbidity and mortality (Farrelly et al, 2013, 2014; Kuiper, Nelson, & Schooley, 2005). It was expected that California would exhibit greater success in tobacco control than the rest of the US, however the differential and strong effects for racial/ethnic minority groups is both striking and an indicator of success in reducing tobacco disparities in California.…”
Section: Discussionmentioning
confidence: 99%
“…With 40% of India's population 16 under the age of 19 years, efforts targeted at curbing tobacco and supari use among adolescents are critical to protect this vulnerable group from addiction and reduce the burden of tobacco-related morbidity and mortality. Tobacco prevention policies and programs have been found to be effective in preventing initiation among adolescents and youth 17,18 . In India, the Cigarettes and Other Tobacco Products Act (COTPA), enacted in 2003, provides directives for the regulation of trade and commerce, advertising, production, supply and distribution of cigarettes and other tobacco products.…”
Section: Introductionmentioning
confidence: 99%
“…While smoke-free policies assist in improving the health of non-smokers they also appear to impact on the health of smokers by reducing the amount of cigarettes smoked per day and to support motivation for cessation [ 5 ]. A US study found smoke-free laws (which included bans in at least one location including workplaces, restaurants and bars) were associated with decreased current and established smoking, but not with past year initiation among young adults [ 13 ]. Others have found total smoking bans to be more likely to promote quit attempts compared to partial smoking bans [ 14 ].…”
Section: Introductionmentioning
confidence: 99%